Pengaruh Viral Marketing dan Kualitas Produk Terhadap Keputusan Pembelian Makanan Kekinian Sang Pisang - Sri Wahyuni; Mariah (UNIVERSITAS KALBIS, 2022)
This study aims to determine the effect of Viral Marketing and product quality on purchasing decisions for contemporary food Sang Pisang. This research is a quantitative research, researchers obtain quantitative data using Google Forms for that is by distributing questionnaires directly to respondents. The Processing Data Used the SPSS Statistics 25 program with a total sample of 162 respondents who live in JABODETABEK with the provision that the respondents had bought Sang Pisang products because the researchers used non-probability sampling and purpose sampling techniques. The results of this study indicate that Viral Marketing and product quality can influence purchasing decisions.